Altering male fertility by manipulating proteases involved in pollen development - Yunus, Muhamad Fahmi (2019)
Male sterility and controlling fertility are considered as valuable traits that can be exploited in agriculture to improve crop productivity by selective breeding and hybrid development. Therefore, understanding the processes of anther and pollen development will not only contribute to the understanding of this process, but also to the development of new varieties for crop production. The formation of viable pollen relies on a specific cell layer in the anther, the tapetum, which is critical for pollen wall development and subsequently goes through programmed cell death (PCD) to facilitate deposition of pollen wall materials and viable pollen formation. Tapetum PCD requires the activity of specific proteases, which are associated with proteolytic breakdown. Seven protease genes and one F-Box protein that showed altered expression patterns in Arabidopsis mutants involved in pollen development have been analysed. These target genes consisted of six Aspartyl- protease (AP) genes (AT1G25510, AT2G23945, AT4G30030, AT5G10760, AT3G20015 and AT5G19120); one cysteine proteinase gene (AT2G21430) and an F-box protein, AT3G16210 gene. Defects in pollen development were seen associated with misexpression of AT2G23945. The work presented in this thesis shows that AT2G23945 is expressed in the anther and when mutated has impaired fertility due to impaired tapetum development. AT2G23945 T-DNA insertion- SALK 135523, showed defective pollen and anther development after analysis of fertility and pollen development using DAPI, Auramine O, ethidium bromide acridine orange, Alexander’s staining and microscopy. To gain insight into the expression pattern of the AT2G23945 gene, transgenic plants carrying the AT2G23945pro:GUS and the AT2G23945pro:AT2G23945:GFP translational fusion were generated. Characterization of the AT2G23945-GUS activity in transgenic Arabidopsis plants indicated different regions of regulatory control in the upstream region. Young silique base is the only region of GUS expression for the construct directed by the short promoter. Constructs with a medium and long promoter resulted in expression in anther tissues as expected. No specific subcellular localization of pUBQ10:AT2G23945:YFP could be determined with expression in the plasma membrane and nucleus, which is identical to the control pUBQ10::YFP construct. Further analysis is needed for transgenic plants harbouring pGKGWG:AT2G23945:GFP.